The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.4018/ijkm.20220101.oa7
|View full text |Cite
|
Sign up to set email alerts
|

Influential Indicators and Measurements of Mediating and Moderating Roles on SME Performance

Abstract: Overcoming the failure of SMEs has been an important research topic. The critical research finding is that it has verified the essential elements of performance improvement. We presented a solution to the research question, "Is there a causal relationship between the effect on SMEs' success on capacity and business performance?". We analyzed whether the competence of SMEs had a mediating effect between success variables and performance. Secondary effects were empirically studied by converting independent varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…This is consistent with arguments related to the liability of aging (Love et al, 2016). However, this result is different from that of Kim (2022) that found that year of establishment showed a positive moderating effect on technical and non-financial performance.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This is consistent with arguments related to the liability of aging (Love et al, 2016). However, this result is different from that of Kim (2022) that found that year of establishment showed a positive moderating effect on technical and non-financial performance.…”
Section: Discussionsupporting
confidence: 83%
“…However, some previous studies need more evidence. Love et al (2016) found that that age somewhat negative impact on performance and Laforet (2013) found that age has not significant effect on performance, while Kim (2022) found that the year of establishment showed a moderating effect on technical and non-financial performance. Thus, there are some inconsistent results on age of business and its moderating role of performance.…”
Section: Moderating Effect Of Age Of Businessmentioning
confidence: 99%
See 1 more Smart Citation
“…The thresholds of construct reliability, validity, and collinearity (Table 3) are met. Values of Cronbach's alpha coefficients are higher than 0.70 (Fitzpatrick et al, 2021), values of Dijkstra-Henseler'srhoA are higher than 0.70 (Kim, 2022), composite reliabilities (CR) are more than 0.70 and less than 0.95, and the values of the average variance extracted (AVE) are higher than 0.50 (Purwanto and Sudargini, 2021). Finally, values of VIF are less than 3 (Hair et al, 2019).…”
mentioning
confidence: 99%